Strategi Penguatan Ilmu Agama bagi Anak TPA di Desa Negeri Sakti melalui Program KKN: Pembelajaran Ngaji dan Praktik Sholat - Fikroh Intan Diansari; Farhan Darmawan; Farhan Muzaki; Faris Faqih Ahmad; Febriana Agatasya; Fia Setiawati; Fifi Mutafia; Fika Rahma Dhania; Fajar Hamdan Nugraha; Nuri Alvin; Siroy Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2025)
Community Service (KKN) activities play a crucial role in community empowerment efforts, particularly in the realm of religious education. This study aims to review the empowerment approach of children in the Al-Qur'an Education Park (TPQ) located in Negeri Sakti Village, Sungkai Barat District, North Lampung Regency through the KKN program, with an emphasis on strengthening religious knowledge through teaching Al-Qur'an reading (mengaji) focused on tajwid and makharijul huruf as well as performing prayer. TPQ is an informal learning space in the field of religion. This TPQ education already exists and is divided into three hamlets located at the Al-Mutawatir Mosque and one of the residents' homes, the children are very enthusiastic about this program. However, there are shortcomings in the teaching system that need to be developed and there is a need for mentoring for teachers. The methodology used includes a qualitative approach with observation techniques. The findings show that the implementation of the KKN program can improve children's ability to read the Al-Qur'an, improve prayer reading, and foster a religious spirit from an early age. Furthermore, collaboration between KKN students, local residents, and TPA teachers in each hamlet is crucial to the program's success. Therefore, teaching Quran reading and prayer through the KKN program has proven to be an effective way to strengthen children's religious foundations and empower the Negeri Sakti village community in the religious field.